2017
DOI: 10.1371/journal.pone.0174802
|View full text |Cite
|
Sign up to set email alerts
|

Clinical contributions of exhaled volatile organic compounds in the diagnosis of lung cancer

Abstract: BackgroundExhaled volatile organic compounds (VOC) are being considered as biomarkers for various lungs diseases, including cancer. However, the accurate measurement of extremely low concentrations of VOC in expired air is technically challenging. We evaluated the clinical contribution of exhaled VOC measured with a new, double cold-trap method in the diagnosis of lung cancer.MethodsBreath samples were collected from 116 patients with histologically confirmed lung cancer and 37 healthy volunteers (controls) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…A total of 139 studies were included in the present review. From the total of 60 cross-sectional clinical studies selected [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], 33 ...…”
Section: Statistics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 139 studies were included in the present review. From the total of 60 cross-sectional clinical studies selected [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ], 33 ...…”
Section: Statistics Of Included Studiesmentioning
confidence: 99%
“…From the total number of participants, 421 were children with 229 children having asthma and 192 children acting as the controls. Of the selected clinical studies, thirty-two of them reported that they used mixed expired breath [ 13 , 17 , 19 , 21 , 33 , 34 , 36 , 38 , 41 , 42 , 43 , 45 , 46 , 54 , 59 , 60 , 61 , 62 , 64 , 66 , 67 , 68 , 69 , 71 , 72 , 73 , 75 , 76 , 78 , 80 , 83 , 85 ] (consisting normally in a mixture of gaseous breath, that also includes the volatile components) collected by simple expiration in bags, tubes with absorbent materials or directly into the used instrumentation (as in the case of E-noses, for example). A total of twenty-two of them reported the use of alveolar breath [ 14 , 15 , 16 , 18 , 22 , 32 , 35 , 37 , 44 , 48 , 56 , 57 , 58 , 65 , 70 , 74 , 77 , 79 , 81 , 82 , 84 , …”
Section: Statistics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cyclohexane has been mentioned in two studies in association with pulmonary diseases. First, Oguma et al described increased levels of cyclohexane (and xylene) in patients with lung cancer compared to healthy controls (after ruling out possible confounders such as age, smoking status, gender and pulmonary function) [ 23 ]. Furthermore, the authors described an increase in cyclohexane (and xylene) levels in breath samples with progressing disease and a decrease in the healing process [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gennaro et al [69] related this finding with the hypothesis of a relationship between reactions of xenobiotic agents' degradation and the neoplastic processes [76,77] as cyclohexane is a metabolite of ε-caprolactam. Cyclohexane has also been proposed to be indicative of oxidative stress in the exhaled breath of lung cancer and colorectal cancer patients [78,79]. However, the exact mechanism underlying its endogenous origin is still not clear.…”
Section: Discussionmentioning
confidence: 99%